2010
DOI: 10.1167/iovs.09-5064
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Correlation between Morphology and Functional Alterations in Diabetic Macular Edema

Abstract: In diabetic macular edema, serous retinal detachment and large ONL cysts are the two morphologic changes with the greatest negative impact on retinal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
1
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 17 publications
9
60
1
9
Order By: Relevance
“…Large cysts in the ONL of the retina in DME are suggested to occur in a rather late stage of DME and have a more severe negative impact on macular function by creating disorganization of photosensitive retinal tissue than smaller cysts or cystoid formation occurring in inner retinal layers. In accordance with previous investigations, our data show clearly that ONL cysts and their size have highest correlations with macular function (BCVA and microperimetry) compared with other evaluated morphological parameters and confirm the results of previous published studies (Deak et al 2010). However, to date, there is only limited data on how this correlation restrains under intravitreal anti-VEGF treatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Large cysts in the ONL of the retina in DME are suggested to occur in a rather late stage of DME and have a more severe negative impact on macular function by creating disorganization of photosensitive retinal tissue than smaller cysts or cystoid formation occurring in inner retinal layers. In accordance with previous investigations, our data show clearly that ONL cysts and their size have highest correlations with macular function (BCVA and microperimetry) compared with other evaluated morphological parameters and confirm the results of previous published studies (Deak et al 2010). However, to date, there is only limited data on how this correlation restrains under intravitreal anti-VEGF treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Mean macular sensitivity seems to correlate significantly with best-corrected visual acuity (BCVA) and may provide additional information about macular function in patients with DME (Deak et al 2010). Apart from functional diagnostics, latest high-resolution optical coherence tomography (OCT) generations allow imaging and evaluation of pathomorphological alterations within the retina of patients with DME (Alasil et al 2010;Nittala et al 2011;Shin et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other variables already known as predictors include age, macular leakage on fluorescein angiography and average fo veal thickening (8,22) . A moderate correlation between RT and VA was sug gested in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…would substantially compromise visual acuity, because the presence of cystoid oedema is an indicator of more serious physiologic disturbance within the retinal neurons, or simply because these spaces can produce optical distortion of the image. In a recent paper, Deak et al 14 reported that in a series of 26 patients with diabetic macular oedema, large intraretinal cystoid spaces and subretinal fluid were the major contributors to visual dysfunction, whereas smaller cystoid spaces were not. However, in a retrospective analysis of a series of patients with diabetic macular oedema who were followed by my colleagues and I at the Kresge Eye Institute and whose retinal imaging records had been collected between 2002 and 2007, Drs Ahmad Aref, Michael Mequio and I found that plots of best-corrected logMAR visual acuity against average thickness of the central 1 mm macular zone measured with the Zeiss-Humphrey Stratus (Carl Zeiss Meditec, Dublin, CA, USA) time-domain optic coherence tomograph (OCT) showed virtually no difference in the linear plots that best fit the data points for patients who had cystoid changes on OCT compared with those who did not (Figure 4).…”
Section: Cystoid Vs Non-cystoid Macular Oedemamentioning
confidence: 99%